2015
DOI: 10.1071/en14202
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated hydrocarbon formation in a moderately acidic salt lake in Western Australia – role of abiotic and biotic processes

Abstract: Environmental context. Volatile halogenated organic compounds (VOX) contribute to ozone depletion and global warming. Here we demonstrate that acidic salt lake sediments in Western Australia contribute to the global natural emission of these compounds and that the emissions are primarily of biotic origin. Elucidating major sources and sinks of VOX is a key task in environmental chemistry because their formation and degradation have major effects on atmospheric chemistry and thus earth climate.Abstract. Volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Boreal forest soils also emit CHCl 3 in similar amounts to that of more southern ecosystems . Substantial emissions of CHCl 3 have also been reported for tundra soil in Alaska, hypersaline sediments, and sediments from a moderately acidic salt lake . In temperate conifer ecosystems, CHCl 3 production is associated with microbial processes in the accumulated organic top layer of the soil .…”
Section: Introductionmentioning
confidence: 97%
“…Boreal forest soils also emit CHCl 3 in similar amounts to that of more southern ecosystems . Substantial emissions of CHCl 3 have also been reported for tundra soil in Alaska, hypersaline sediments, and sediments from a moderately acidic salt lake . In temperate conifer ecosystems, CHCl 3 production is associated with microbial processes in the accumulated organic top layer of the soil .…”
Section: Introductionmentioning
confidence: 97%
“…The formation of ozone-degrading volatile halogenated hydrocarbons (VOX) has been shown to occur in many environments like salt lake sediments, marine environments and forest soils (Albers et al 2010;Ruecker et al 2014Ruecker et al , 2015Yang et al 2014). Particularly in soils, the existence of an active natural chlorine cycle has been demonstrated ( € Oberg 2002;€ Oberg and Sand en 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The terrestrial compartment section commences with Rücker et al [5] who present results from Western Australian salt lakes. They quantified VOX emissions from an acidic salt lake in biotic and abiotic microcosm experiments under controlled laboratory conditions and revealed that biota is the main driver of halogenation processes.…”
mentioning
confidence: 99%